A problem of scope for the free energy principle as a theory of cognition. (2nd October 2016) - Sims, Andrew
Abstract: Those who endorse the free energy principle as a theory of cognition (as well as a theory of biological homeostasis) are committed to three propositions that are jointly incompatible but which will cohere if one of them is denied. The first of these is that the free energy principle gives us a self-sufficient explanation of what all cognitive systems consist in: a specific computational architecture. The second is that all adaptive behavior is driven by the free energy principle and the process of model-based inference it entails. The third is that cognition is not ubiquitous. These three incompatible propositions together comprise a problem of scope for the free energy principle as a theory of cognition. The prospects for rejecting each of these propositions are considered. To drop either the first or the second would limit the explanatory success of the principle. However, there are plausible ways to bite the bullet on denial of the third proposition. In particular, I argue that it is possible for the free energy theorist to admit that cognition is ubiquitous in biological systems while reserving conceptual space exclusively for human cognitive capacities.